A stromal cell-derived factor-1 releasing matrix enhances the progenitor cell response and blood vessel growth in ischaemic skeletal muscle - D Kuraitis (European Cells & Materials, 2011)
Although many regenerative cell therapies are being developed to replace or regenerate ischaemic muscle, the lack of vasculature and poor persistence of the therapeutic cells represent major limiting factors to successful tissue restoration. In response to ischaemia, stromal cell-derived factor-1 (SDF-1) is up-regulated by the affected tissue to stimulate stem cell-mediated regenerative responses. Therefore, we encapsulated SDF-1 into alginate microspheres and further incorporated these into an injectable collagen-based matrix in order to improve local delivery. Microsphere-matrix impregnation reduced the time for matrix thermogelation, and also increased the viscosity reached. This double-incorporation prolonged the release of SDF-1, which maintained adhesive and migratory bioactivity, attributed to chemotaxis in response to SDF-1. In vivo, treatment of ischaemic hindlimb muscle with microsphere-matrix led to increased mobilisation of bone marrow-derived progenitor cells, and also improved recruitment of angiogenic cells expressing the SDF-1 receptor (CXCR4) from bone marrow and local tissues. Both matrix and SDF-1-releasing matrix were successful at restoring perfusion, but SDF-1 treatment appeared to play an earlier role, as evidenced by arterioles that are phenotypically older and by increased angiogenic cytokine production, stimulating the generation of a qualitative microenvironment for a rapid and therefore more efficient regeneration. These results support the release of implanted SDF-1 as a promising method for enhancing progenitor cell responses and restoring perfusion to ischaemic tissues via neovascularisation.